What's hatching out of that egg? - Lauber, Patricia frey50 (Crown Publishers, Inc. New York, 1979)
Text and illustrations introduce a variety of eggs and the animals that hatch out of them. Includes ostrich, python, bullfrog, and monarch butterfly eggs among others.
Keywords: Animals -- Infancies of -- Juvenile literature; Reproduction -- Juvenile literature